Solar Systems for Manufacturers: Evidence from Northern Cyprus - Şenyiğit, Deniz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
From the past few decades, the use of fossil fuels has observed a significant increase, causing a serious threat to future resources. Countries have started relying on non renewable resources for energy generation, which has led to the world’s pollution, severe climate changes, and high carbon emissions. This is important and vital in the process of achieving sustainable development. Cyprus, the third-largest island in the Mediterranean, is also facing this issue. Researchers have conducted various studies to determine the financial and operational viability of solar energy and wind for producing energy. The market of solar panels production is constantly growing, owing to increased demand for energy generation sources from renewable resources. Literature analyses showed that fossil fuels have significantly damaged the environment and therefore, many other energy resources are considered to produce electricity for achieving sustainable development. Electricity is argued to be a costly input for the industry in North Cyprus which has negative impacts on the productivity and competitiveness of especially manufacturers. In this thesis we argue that if manufacturers use solar systems to generate electricity, it will help them to reduce one of their input costs. In this respect, feasibility analyses are made for two different projects which are for 2,5 and10 MW capacity of solar power systems. Findings reflect that NPV for 2,5 MW of solar system is positive being 1.280.396 Euros and an IRR higher than discount rate, as 27%. We also carry out a feasibility analysis for 10 MW as well and find that NPV is 5.418.014 Euros and IRR of 28%. These results show that both project are feasible and a profitable investments. As for risk, sensitivity analysis shows that in 2,5 MW project, only when the production of solar systems fall by 40% and more, the NPV will turn to negative. There is no risk for the project in relation to price and other variables. We also find that 10 MW capacity of solar power project has relatively lower risk in relation to production and price. As a whole, the results of the financial analysis for the solar systems show that the non-renewable energy sources do have positive financial implications along with a reduction in the carbon footprints for the corporate world. As for the manufacturers in North Cyprus who consumes around 83.000 MWh yearly, we show with this study that they these projects can supply 5% and 21% of this consumption respectively and can reduce their energy costs significantly. The implications of these findings call for the policy makers and the governments to support and encourage manufacturers to build solar farms. This can be done by providing more convenient financial means and by giving permits to manufacturers.

ÖZ: Son yıllardaki fosil yakıt kullanımı kayda değer bir şekilde artmış olup, dünyanın gelecekteki kaynakları için ciddi bir tehlike yaratmıştır. Ülkelerin enerji üretimi için yenilenebilir olmayan kaynaklarına yönelmesi, dünyada hava kirliliğine, şiddetli iklim değişikliklerine ve yüksek karbon emisyonlarına yol açmaktadır. Akdeniz’de üçüncü en büyük ada olan Kıbrıs da bu sorunlarla yüzleşmektedir. Araştırmacılar güneş ve rüzgar ile elektrik enerji üretiminin finansal ve uygulanabilirliklerini belirlemek için çeşitli araştırmalar yapmıştır. Yenilenebilir kaynaklardan enerji üretimine olan ilgi arttığından dolayı güneş panelleri ile enerji üretimi sürekli şekilde artış göstermektedir. Yenilenebilir enerji üretimleri sürdürülebilir kalkınmaya da destek vermektedir. Kuzey Kıbrıs’ta elektrik üretimi maliyetlidir. Bu durum özellikle sanayi sektörünün verimliliğini ve rekabet edebilirliğini olumsuz etkilemektedir. Bu tezde, sanayi sektöründeki imalatçıların ihtiyaç duydukları elektrik enerjisini güneş enerji sistemleri kullanarak üretmelerinin girdi maliyetlerini azaltmalarına yardımcı olabileceği savunulmaktadır. Bu kapsamda 2.5 ve 10 MW kapasiteli iki farklı güneş enerji sistemleri projelerinin fizibilite analizleri yapılmıştır. Sonuçlar, 2.5 MW’lık solar sistemi için Net Bugünkü Değer’in (NPV) 1.280.396 Avro ve İç Verim Oranının (IRR) yüzde 27 olup paranın maliyetini gösteren iskonto değerinden daha fazla olduğunu göstermektedir. Ayrıca, 10 MW’lık sistemin Net Bugünkü Değer’in 5.418.014 Avro ve İç Verim Oranının %28 olduğu hesaplanmıştır. Bu sonuçlar, her iki projenin de uygulanabilir ve karlı olduğunu göstermektedir. Projelerin riskini belirlemek için yapılan duyarlılık analizi, solar enerji üretiminin yüzde 40 ve daha düşük seviyede olması durumunda, 2.5 MW’lık projenin negatif Net Bugünkü Değer ile karşı karşıya kalacağını göstermektedir. Bu da projenin üretim miktarına duyarlı olduğunu göstermektedir. Üretilecek enerjinin satış fiyatı ve diğer değişkenlerin her iki sistemdeki proje için herhangi bir risk taşımadığı ve bunlara duyarlı olmadığı tespit edilmiştir. Ölçek olarak daha büyük olan 10 MW’lık sistemde riskin çok daha düşük olduğu tespit edilmiştir. KKTC’deki imalatçıların 2018 yılında enerji tüketiminin yıllık 83.000 MWh civarında olduğu dikkate alınırsa, 2.5 MW ve 10 MW sistemlerinin hayata geçmesi ile tüketimlerinin sırasıyla yüzde 5 ve yüzde 20’sini karşılayabilecektir. Sonuç olarak, yenilenebilir enerji kaynakları finansal açıdan karlı olup, iş dünyasında büyük şirketlerin karbon salımının azalmasını sağlaması yanında maliyetlerini de azaltacaktır. Özellikle imalatçıların solar sistemlerini kullanmaları enerji maliyetlerinin azaltılmasına ve rekabet edebilirliklerinin artmasını sağlayacaktır. Bu tespitlerle politika geliştiricileri ve hükümetlerin bu tür projeleri desteklemesi ve teşvik etmesi gerektiğini göstermektedir. Bu destekler imalatçılara daha uygun finansman kaynakları sağlayarak ve solar enerji üretimi için daha çok izin vermeleri ile gerçekleştirilebilecektir.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2020. Supervisor: Prof. Dr. Mustafa Besim
Keywords: Banking and Finance Department; Solar Energy--Solar Systems--Renewable energy resources--Energy Economics; Electricity, Solar Systems, Renewable Energy, Manufacturers, Net Present Value, Internal Rate of Return, Sensitivity Analysis